A proposal to measure the similarity between retinal vessel segmentations images - Marco A. Escobar; José R. Guzmán Sepúlveda; Jorge R. Parra Michel; Rafael Guzmán Cabrera (Nova Scientia, 2019)
Introduction: We propose a novel approach for the assessment of the similarity of retinal vessel segmentation images that is based on linking the standard performance metrics of a segmentation algorithm, with the actual structural properties of the images through the fractal dimension.